Modifications of sugarcane bagasse-derived adsorbents to enhance the adsorption of microalgae biomass in easing harvesting process - Basri, W.N.F.W. (American Institute of Physics Inc., 2017)
Recently, the attempt to create adsorbents in solving various separation problems has intensified drastically. The proposal of present research lightens the way to enhance the microalgae biomass harvesting process with the addition of sugarcane bagasse-derived adsorbent in culture medium. The adsorbents were tested with several chemical activations and concentrations to determine the optimum ones. Acid modified adsorbents with concentration of 1.0M and 1.5M demonstrated the highest adsorption with attainable biomass adsorption capacities 66 for both. The samples viewed under SEM showed 1.0M and 1.5M acid modified adsorbents have highest microalgae adsorption. © 2017 Author(s).